Changing landscape of liver transplant in the United States—time for a new innovative way to define and utilize the “non-standard liver allograft”—a proposal - Seth, Rashmi; Andreoni, Kenneth A. (Frontiers in Transplantation, 2024)
Since the first liver transplant was performed over six decades ago, the landscape of liver transplantation in the US has seen dramatic evolution. Numerous advancements in perioperative and operative techniques have resulted in major improvements in graft and patient survival rates. Despite the increase in transplants performed over the years, the waitlist mortality rate continues to remain high. The obesity epidemic and the resultant metabolic sequelae continue to result in more marginal donors and challenging recipients. In this review, we aim to highlight the changing characteristics of liver transplant recipients and liver allograft donors. We focus on issues relevant in successfully transplanting a high model for end stage liver disease recipient. We provide insights into the current use of terms and definitions utilized to discuss marginal allografts, discuss the need to look into more consistent ways to describe these organs and propose two new concepts we coin as “Liver Allograft Variables” (LAV) and “Liver Allograft Composite Score” (LACS) for this. We discuss the development of spectrum of risk indexes as a dynamic tool to characterize an allograft in real time. We believe that this concept has the potential to optimize the way we allocate, utilize and transplant livers across the US.